2016
DOI: 10.1007/s00115-016-0261-3
|View full text |Cite
|
Sign up to set email alerts
|

Zwangsmaßnahmen in deutschen Kliniken für Psychiatrie und Psychotherapie

Abstract: Suitable measurement instruments and reliable data that enable the learning of best practices represent the basis for a reduction of coercive measures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
2
0
10

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 17 publications
3
2
0
10
Order By: Relevance
“…This is the first study that evaluated the implementation of the Safewards Model in locked acute psychiatric wards in the German health care context with regard to coercive measures. The characteristics of the patient population regarding age range and distribution are in line with numerous other surveys, e.g., a study by Adorjan et al that evaluated the use of coercive measures in eight German psychiatric hospitals (58). Other studies also found coercive measures to be most commonly used in patients with schizophrenia (59) followed by patients with substance use disorders (58, 60).…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…This is the first study that evaluated the implementation of the Safewards Model in locked acute psychiatric wards in the German health care context with regard to coercive measures. The characteristics of the patient population regarding age range and distribution are in line with numerous other surveys, e.g., a study by Adorjan et al that evaluated the use of coercive measures in eight German psychiatric hospitals (58). Other studies also found coercive measures to be most commonly used in patients with schizophrenia (59) followed by patients with substance use disorders (58, 60).…”
Section: Discussionsupporting
confidence: 78%
“…The characteristics of the patient population regarding age range and distribution are in line with numerous other surveys, e.g., a study by Adorjan et al that evaluated the use of coercive measures in eight German psychiatric hospitals (58). Other studies also found coercive measures to be most commonly used in patients with schizophrenia (59) followed by patients with substance use disorders (58, 60). A further German study found patients with an organic mental disorder to be most commonly exposed to coercive measures followed by patients with a schizophrenic disorder (12).…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Es gibt unseres Wissens keinerlei empirische Schätzungen des Bedarfs an ethischer Beratung in Krankenhäusern. Nimmt man allerdings als Grundlage für eine Schätzung nur die Häufigkeit von 0,5 % Zwangsbehandlungen [11], so wäre in einer durchschnittlich großen Klinik mit 3000 stationären Patienten pro Jahr mit 15 Zwangsbehandlungen zu rechnen. Nimmt man nun an, dass zumindest in der Hälfte dieser Fälle relevante moralische Konflikte bestehen dürften, errechnet sich aus nur diesem einen Anwendungsbeispiel ein Bedarf der mehr als doppelt so hoch ist, wie der Median tatsächlich durchgeführter Beratungen.…”
Section: Diskussionunclassified
“…Hieraus ergibt sich die ethische Fragestellung, ob und wie der Wille des Patienten bestimmt und das Vorgehen gestaltet werden kann, ob und wie die Wünsche des nicht Einwilligungsfähigen berücksichtigt werden können. Ein seltener, aber besonders gravierender ethischer Konflikt ergibt sich immer dann, wenn zu klären ist, ob eine indizierte medizinische Behandlung zum Wohl des Patienten gegen seinen natürlichen Willen durchgesetzt werden soll oder nicht, ob also eine Zwangsbehandlung durchgeführt werden soll, was doch immerhin bei 0,5 % der Krankenhauspatienten geschieht [11]. Ferner sind im psychiatrischen Umfeld auch Abwägungen zwischen den Prinzipien des Wohltuns und des Nichtschadens von großer Bedeutung, zum Beispiel bei langfristiger Behandlung mit Psychopharmaka [12].…”
Section: Introductionunclassified